Reproductive cycle of Mytella guyanensis (Lamarck, 1819) in a Marine Reserve (RESEX Bay of Iguape), Bahia, Brazil - V. M. A. Camilo; J. da C. Souza; E. de J. Conceição; J. R. Luz; G. Boehs; S. Campiolo (Brazilian Journal of Biology, 2017)
Abstract Mytella guyanensis, consumed and commercialized in coastal regions of Brazil, is one of several bivalve species of socioeconomic interest for coastal communities. Besides serving as a source of income and subsistence for these communities, it also contributes to their food security as it is a source of proteins and micronutrients. Thus, the reproductive cycle of this species was studied aiming to contribute to food security and its preservation. Samples were collected monthly, between March 2014 and March 2015, in a natural stock (12°38'50”S; 38°51'43”W) in a Marine Reserve (RESEX Bay of Iguape) (community Engenho da Ponte), Bahia, Brazil. Mytella guyanensis is collected by women on site, where the artisanal fishing of this resource is performed without following any specific handling procedure. Also, empirical evidence indicates overexploitation. The specimens collected were measured along the anterior-posterior axis (length), and after macroscopic analysis they were fixed in Davidson solution, processed by routine histology techniques and stained with Harris haematoxylin and eosin (H&E). The macroscopic analysis showed sexual dimorphism, with the male and female gonads presenting a milky-white and orange colour, respectively. A 1:1 sex ratio (M: F) was observed and reproduction of the species was continuous all year round. March, April, July and August were the months with highest values of gamete elimination. We suggest that a M. guyanensis management plan should restrict capture during these months, in order to sustainably regulate exploitation of this food resource in this reserve.